2014
DOI: 10.2139/ssrn.2423387
|View full text |Cite
|
Sign up to set email alerts
|

LIBOR: Origins, Economics, Crisis, Scandal, and Reform

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The LIBOR is a benchmark rate, or rather a set of rates, that indicates how much interest would be paid by large banks when they borrow short-term funds from other banks on the money markets, for a given period, in a given currency. At the time of the financial crisis, the LIBOR was the most closely watched number on the planet because it serves two crucial functions in the financial markets: (1) it is a reference rate for a range of financial contracts, and (2) it is an indicator of the financial ‘health’ of systemically important banks (Hou and Skeie, 2014; Koblenz et al, 2013). First, as a reference rate, the LIBOR is used in many financial contracts, including various retail loan and mortgage agreements, and, importantly for the benchmarks manipulation, as the basis of a range of derivatives contracts (contracts whose value depends on the movement of another underlining asset – Koblenz et al, 2013).…”
Section: Unpacking the Benchmarks: The Functioning And Fixing Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…The LIBOR is a benchmark rate, or rather a set of rates, that indicates how much interest would be paid by large banks when they borrow short-term funds from other banks on the money markets, for a given period, in a given currency. At the time of the financial crisis, the LIBOR was the most closely watched number on the planet because it serves two crucial functions in the financial markets: (1) it is a reference rate for a range of financial contracts, and (2) it is an indicator of the financial ‘health’ of systemically important banks (Hou and Skeie, 2014; Koblenz et al, 2013). First, as a reference rate, the LIBOR is used in many financial contracts, including various retail loan and mortgage agreements, and, importantly for the benchmarks manipulation, as the basis of a range of derivatives contracts (contracts whose value depends on the movement of another underlining asset – Koblenz et al, 2013).…”
Section: Unpacking the Benchmarks: The Functioning And Fixing Of The mentioning
confidence: 99%
“…Despite increased scrutiny of the financial markets following the global financial crisis and the mobilization of law enforcement efforts, scandals such as the rigging of the LIBOR (London InterBank Offered Rate) (Wheatley, 2012) and Forex (foreign exchange) (Tillman et al, 2018), trading benchmarks by global investment banks indicate that the financial services industry was still affected by serious, pervasive and networked corporate crimes. The LIBOR came under public scrutiny at the height of the financial crisis with allegations that banks had deliberately misstated their LIBOR submissions to project financial soundness during market turbulence (Hou and Skeie, 2014). The ensuing investigations revealed that the manipulations had preceded the crisis and uncovered a range of rigging activities undertaken by multiple, systemically important participants in the financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of the US LIBOR rate came under fire in June 2012 when Barclays Bank, UBS, RBS, and Rabobank allegedly under-reported their borrowing costs (Hou and Skeie, 2014). This raises questions over the stability of the financial system, robustness and effectiveness of reference rates, and credibility of financial regulators (Gyntelberg and Wooldridge, 2008).…”
Section: The Libor Manipulation and Its Likely Effect On The Magnitudmentioning
confidence: 99%
“…Due to limited availability of interbank bid and ask yields we use the Eurodollar deposit bid and ask rates as a proxy [47].…”
Section: Liquidity Spreadmentioning
confidence: 99%